IMPROVING STUDENTS' CRITICAL THINKING SKILLS THROUGH A PROBLEM-BASED APPROACH - Lisyah Ramadhani (Teaching and General Education Studies, 2026)
Critical thinking skills are one of the essential competencies that students must master in facing the challenges of the 21st century. However, various assessment results both national and international show that the critical thinking skills of students in Indonesia are still relatively low. This review article aims to analyze the effectiveness of the Problem Based Learning (PBL) model in improving students' critical thinking skills based on the synthesis of empirical research results published between 2020 and 2025. The method used was a systematic literature review (SLR) of 15 articles from SINTA-accredited national journals and reputable international journals Scopus and Web of Science. Inclusion criteria include: (1) experimental or quasi-experimental research, (2) using PBL as an independent variable, (3) critical thinking as a bound variable, and (4) research subjects are elementary to high school/vocational students. The results of the study show that PBL has consistently been proven to be effective in improving students' critical thinking skills at various levels of education and subjects. The average increase in critical thinking N-gain in PBL classes ranged from 0.40 to 0.72 (medium to high category). The success factors of PBL include the quality of authentic problem design, teacher facilitation ability, availability of learning resources, and student motivation. The implications of this study provide practical recommendations for teachers in implementing PBL effectively as well as for researchers to explore moderator variables that affect the effectiveness of PBL.